PENGARUH EFISIENSI OPERASIONAL TERHADAP KINERJA BANK YANG TERDAFTAR DI BEI PERIODE 2007 - 2010 - Asih Fatmawati, 10.05.51.0135; Sudiyatno, Bambang (Students Journal of Economic and Management, 2012)
The study was conducted to examine the influence of the operational efficiency of the performance of banks listed on the Indonesia stock exchange the period 2007 - 2010. Samples taken in this study as many as 96 companies and banks have active stock during the years 2007-2010. To obtain information needed to do the data collection process through documentation. In the method of data collection is to make copies by means of collecting archives and corporate records. Techniques of data analysis study is a test for normality, and the assumption of classical testÂ multikolonieritas, hteroskedastisitas test, test autokolerasi. Multiple linear analysis used in this study to determine the influence of CAR, BOPO and LDR to ROA. The analysis shows that the financial ratios of the CAR and the LDR does not have a significant impact on the banking companys ROA during the period 2007-2010 at the level of significance greater than 5%, while the ratioBOPO ROA has a significant influence on corporate banking in Indonesia Stock Exchange. The predictive capability of these three variables on ROA of 18.8% as has been demonstrated by the adjusted R square of 0.188. While the remaining 81.2% described in other variables beyond the research model. Key words: Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), Loan to Deposit Ratio (LDR dan Return on Assets (ROA).